How the active learning method affects students' desire to learn - Agueda Eustaqio; Mauli da Gorráitz; Sarmento Calos Lora (Trigin Institute, 2022)
Researchers found that a mean score of 12.24 was achieved when measuring the level of student enthusiasm to learn while using an active learning strategy. Students whose education follows the traditional model report an average (mean) level of motivation to learn of 11.2. The